2014
DOI: 10.1177/0022146514556509
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation, Internal Migration, and Mental Health during the Transition to Adulthood

Abstract: Previous research has suggested that sexual minorities may have higher rates of migration than heterosexuals, indicating their effort to escape stigma in the currently residing areas. However, direct evidence for the migration pattern has been lacking, and mental health implications of such coping effort have been unclear. This study seeks to fill these gaps in the literature by analyzing the Add Health data, which include longitudinal measures of residential locations, sexual orientation, and mental health. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 75 publications
1
14
0
1
Order By: Relevance
“…Previous research has found mixed evidence that gay men and lesbian women migrate in response to the passage of pro-gay laws. Ueno et al (2014) found that gay men were no more likely than heterosexual men to migrate to a different state, but lesbian women are more likely than heterosexual women to move. When gay men and lesbian women do move, there is inconclusive evidence that gay rights laws influence their choices.…”
Section: Datamentioning
confidence: 96%
“…Previous research has found mixed evidence that gay men and lesbian women migrate in response to the passage of pro-gay laws. Ueno et al (2014) found that gay men were no more likely than heterosexual men to migrate to a different state, but lesbian women are more likely than heterosexual women to move. When gay men and lesbian women do move, there is inconclusive evidence that gay rights laws influence their choices.…”
Section: Datamentioning
confidence: 96%
“…Conversely, other studies have found living in a gay neighborhood was associated with methamphetamine use and condomless receptive anal intercourse, while protective against substance use dependency [14,15]. A lack of significant neighborhood gay presence may result in gay and bisexual men migrating into urban areas to seek a more supportive, less homophobic environment [16,17]. At the same time, gay and bisexual men born and raised in large urban areas such as New York City (NYC) also report challenging experiences of homophobia and heterosexism in neighborhoods with little gay space.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual orientation has been linked to adolescent mental and physical health, with lesbian, gay and bisexual (LGB) adolescents faring worse than heterosexual adolescents (for recent reviews see Institute of Medicine 2011 ; Mustanski 2015 ). Depressive symptoms rank among the most frequently studied mental health outcomes related to sexual orientation (Almeida et al 2009 ; Jiang et al 2010 ; Ueno et al 2014 ; Wang et al 2014 ). Cross-sectional studies have found higher levels of depressive symptoms for LGB people in comparison to heterosexuals, in adolescence (Marshal et al 2011 ) as well as adulthood (Institute of Medicine 2011 ; Meyer 2003 ).…”
Section: Introductionmentioning
confidence: 99%